Understanding and Managing Millennial Employees in the Private Sector: Exploring the Mediating Effects of Organizational Commitments and Job Satisfaction - Nabiilah, Fidaa; Luturlean, Bachruddin Saleh; Pradana, Mahir (Journal of Ecohumanism, 2024)
This research aims to understand and manage millennial employees in the private sector in Bandung, Indonesia, with a focus on variables such as job satisfaction, turnover intention, job mismatch, and organizational commitment. The study adopts a quantitative approach with causal analysis. Data were collected from millennial employees working in private companies in Bandung through the distribution of questionnaires, which were then processed and analyzed. The results indicate significant relationships among these variables, with important implications for job satisfaction, job mismatch, turnover intention, and organizational commitment. This research provides valuable insights for private companies in Bandung to understand and manage millennial employees, contributing to broader goals of creating a sustainable and inclusive work environment.